2005
DOI: 10.1152/japplphysiol.00479.2004
|View full text |Cite
|
Sign up to set email alerts
|

Vascular growth and remodeling in compensatory lung growth following right lobectomy

Abstract: Studies in animal models have shown that, following lobectomy (LBX), there is compensatory growth in the remaining lung. The vascular growth response following right LBX (R-LBX) is poorly understood. To test the hypothesis that arterial growth and remodeling occur in response to LBX, in proportion to the amount of right lung tissue removed, two (24% of lung mass; R-LBX2 group) or three right lobes (52% of lung mass; R-LBX3 group) were removed via thoracotomy from adult rats. Sham control animals underwent thor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 24 publications
2
31
0
1
Order By: Relevance
“…Support for the role of angiogenesis in the development of lung tissue can be found in studies showing that the anti-angiogenic agents fumagillin, thalidomide, and SU-5416 attenuate vascular growth and reduce alveolarization in developing rat lung (15). Additionally, it has been shown that compensatory vascular growth in lung tissue is proportional to the amount of tissue removed during pneumonectomy (21). Taken together, this research suggests a significant role for angiogenesis in both the normal development and compensatory growth of the lung.…”
mentioning
confidence: 98%
“…Support for the role of angiogenesis in the development of lung tissue can be found in studies showing that the anti-angiogenic agents fumagillin, thalidomide, and SU-5416 attenuate vascular growth and reduce alveolarization in developing rat lung (15). Additionally, it has been shown that compensatory vascular growth in lung tissue is proportional to the amount of tissue removed during pneumonectomy (21). Taken together, this research suggests a significant role for angiogenesis in both the normal development and compensatory growth of the lung.…”
mentioning
confidence: 98%
“…When a bilobectomy was performed in rats (24% of lung tissue removed), the arterial area of the remaining lung increased by 26% compared to sham animals. Furthermore, when lung resection was more extensive (trilobectomy, 52%) we found that the increase in arterial area increased by 47% (Le Cras, et al, 2005). Other researchers have shown the effects of exogenous angiogenic factors, such as vascular endothelial growth factor (VEGF) in the mouse model.…”
Section: Vascular Growth and Angiogenesismentioning
confidence: 66%
“…Our laboratory has shown that angiogenesis is necessary for successful CLG by demonstrating that angiogenesis inhibitors such as fumagillin or thalidomide prevented increased lung weight and volume after pneumonectomy (Maxey, et al, 2003). We have also shown that pneumonectomy induces arterial growth including the increase in length and number of branches of pulmonary arteries and that these changes are proportional to the amount of tissue removed (Le Cras, et al, 2005). When a bilobectomy was performed in rats (24% of lung tissue removed), the arterial area of the remaining lung increased by 26% compared to sham animals.…”
Section: Vascular Growth and Angiogenesismentioning
confidence: 74%
“…1). Arterial density, length, and surface area increase as blood flow to the remaining lung doubles [3,27,28]. Compensatory lung growth cannot occur without appropriate generation of functional gasexchange regions, which also requires significant and immediate peripheral blood vessel growth.…”
Section: Discussionmentioning
confidence: 99%